Service quality and store atmosphere on customer satisfaction and repurchase intention - Santirianingrum Soebandhi; Abdul Wahid; Ira Darmawanti (Universitas Negeri Surabaya, 2020)
Nowadays, consumers are not only looking for good tastes, but they are also looking for a cosy cafe atmosphere and satisfying service. The high competition in the culinary business has forced entrepreneurs to offer different concepts to attract customers. This study will give an account of analyzing the role of cafe atmosphere, service quality and customer satisfaction in customer purchase intention in thematic cafe in Surabaya. This study involved 150 respondents with PLS-SEM was used to analyze the data. The analysis shows that all of the hypotheses proposed are supported. The results of this study also present that, compared to service quality, the cafe atmosphere has a stronger effect on customer satisfaction, leading to repurchase intention of the customers.